THE ROLE OF THE DIGITAL ECONOMY TODAY AND IMPORTANCE - Umataliyev Farruxbek Umarjon o’g’li (Ecomind Press, 2025)
Currently, in many developed countries, the digital economy and their development have a significant impact on the factors of development, and the digital economy also plays an important role in the life of society. This scientific article will talk about the role and significance of the digital economy.
Keywords: Digital transformation, digital technology, socio-economic, society, information, products.